Acts of citizenship? rulers and ruled in traditional Bali. Issue 3 (3rd April 2019) - Creese, Helen
ABSTRACT: Recent understandings of indigenous leadership and governance have reframed earlier dualistic depictions of precolonial Balinese governance in terms of despotic kingship on the one hand and autonomous village society on the other. This article draws on indigenous literary, legal and political texts in conversation with contemporaneous nineteenth-century Western depictions of the island to re-examine notions of premodern Balinese citizenship. Political, social and ritual practices that bound together ruler and ruled in a shared community enabled a level of participation in rule by the ruled and acted as a curb on excessive arbitrary justice. A number of social and political institutions suggest nascent forms of modern citizenship. They include a representative voice at the village level, written laws and formal legal processes, the right to petition and the right of dissatisfied followers to move away and seek the protection of a neighbouring lord, a system known as matilas .